Dentine biomodification by sulphonamides pre-treatment: bond strength, proteolytic inhibition, and antimicrobial activity - Maristela Barbosa Portela; Caroliny Mello Barboza; Eduardo Moreira da Silva; Daniel Clemente de Moraes; Renata Antoun Simão; Clara Ribeiro de Souza; Verônica da Silva Cardoso; Antônio Ferreira-Pereira; Alane Beatriz Vermelho; Claudiu T. Supuran (Taylor & Francis Group, 2023)
We evaluated the effects of dentine biomodification after pre-treatment with two sulphonamide carbonic anhydrase inhibitors (CAIs) of the N-[4-sulphamoylphenethylcarbamoyl]benzenesulphonamide type, investigating matrix metalloproteases activity, resin-dentine micro tensile bond strength, dentine surface wettability, and antimicrobial activities. Ninety-five sound-extracted human molars were selected for the study. Inhibitory effects were evaluated by gelatinase and collagenase activity tests and collagen degradation FT-IR spectroscopic analysis. Pre-treatment with the two CAIs kept the micro tensile values after 12 months of storage (32.23 ± 5.95) and cariogenic challenge (34.13 ± 2.71) similar to the initial, pre-treatment values (33.56 ± 4.34). A decreased Streptococcus mutans biofilm formation on dentine surfaces and antibacterial activity against planktonic bacteria were observed after CAI treatment. Dentine pre-treatment with sulphonamide CAIs maintained adhesion strength stability, allowed better dentine wettability, maintained matrix collagen, and showed anti-S. mutans activity.